Work ability as prognostic risk marker of disability pension: single-item work ability score versus multi-item work ability index - Roelen, Corné AM; van Rhenen, Willem; Groothoff, Johan W; van der Klink, Jac JL; Twisk, Jos WR; Heymans, Martijn W (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVES ': 'Work ability predicts future disability pension (DP). A single-item work ability score (WAS) is emerging as a measure for work ability. This study compared single-item WAS with the multi-item work ability index (WAI) in its ability to identify workers at risk of DP. ' ' METHODS ': 'This prospective cohort study comprised 11 537 male construction workers, who completed the WAI at baseline and reported DP after a mean 2.3 years of follow-up. WAS and WAI were calibrated for DP risk predictions with the Hosmer-Lemeshow (H-L) test and their ability to discriminate between high- and low-risk construction workers was investigated with the area under the receiver operating characteristic curve (AUC). ' ' RESULTS ': 'At follow-up, 336 (3%) construction workers reported DP. Both WAS [odds ratio (OR) 0.72, 95% confidence interval (95% CI) 0.66–0.78] and WAI (OR 0.57, 95% CI 0.52–0.63) scores were associated with DP at follow-up. The WAS showed miscalibration (H-L model χ²=10.60; df=3; P=0.01) and poorly discriminated between high- and low-risk construction workers (AUC 0.67, 95% CI 0.64–0.70). In contrast, calibration (H-L model χ²=8.20; df=8; P=0.41) and discrimination (AUC 0.78, 95% CI 0.75–0.80) were both adequate for the WAI. ' ' CONCLUSION ': 'Although associated with the risk of future DP, the single-item WAS poorly identified male construction workers at risk of DP. We recommend using the multi-item WAI to screen for risk of DP in occupational health practice.
Keywords: construction worker; disability pension; discriminative ability; prognostic research; prognostic risk marker; risk marker; ROC curve; sensitivity; single-item workability score; specificity; WAI; WAS; work ability; work ability index